2012
DOI: 10.1093/cid/cis1022
|View full text |Cite
|
Sign up to set email alerts
|

Standard Treatment Regimens for Nongonococcal Urethritis Have Similar but Declining Cure Rates: A Randomized Controlled Trial

Abstract: Clinical and microbiologic cure rates for NGU were somewhat low and there was no significant difference between azithromycin and doxycycline. Mycoplasma genitalium treatment failure was extremely common. Clinical Trials Registration.NCT00358462.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
183
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(194 citation statements)
references
References 27 publications
6
183
2
3
Order By: Relevance
“…The prevalence of pathogens identified in both studies is reassuringly similar, and these data confirm C. trachomatis and M. genitalium are less likely to be detected in MSM. The estimates for C. trachomatis and M. genitalium are also in keeping with other estimates from our service and region (17)(18)(19)(20). It was interesting to note that even in the presence of a bacterial pathogen, MSM reported more consistent condom use for anal sex than MSW for vaginal sex and that MSM with idiopathic NGU were also substantially more likely to report engaging in only nonpenetrative anal/ vaginal sexual activity with their partners in the prior 3 months.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of pathogens identified in both studies is reassuringly similar, and these data confirm C. trachomatis and M. genitalium are less likely to be detected in MSM. The estimates for C. trachomatis and M. genitalium are also in keeping with other estimates from our service and region (17)(18)(19)(20). It was interesting to note that even in the presence of a bacterial pathogen, MSM reported more consistent condom use for anal sex than MSW for vaginal sex and that MSM with idiopathic NGU were also substantially more likely to report engaging in only nonpenetrative anal/ vaginal sexual activity with their partners in the prior 3 months.…”
Section: Discussionsupporting
confidence: 83%
“…This study, to our knowledge, is the first to investigate macrolide susceptibility among low-risk women and suggests that M. genitalium strains circulating in this population are more susceptible to these antibiotics than those in higherrisk populations such that AZM is less effective (12,47). AZM treatment failures using the 1-g dose have ranged from 15 to 60% (47)(48)(49).…”
Section: Discussionmentioning
confidence: 88%
“…Since AZM is commonly used to treat male NGU and is also included in the current CDC treatment guidelines for gonorrheae, it remains imperative to monitor resistance patterns for M. genitalium and other bacterial STIs since virtually all men with urethritis receive AZM. In patients with AZM-resistant M. genitalium infections, moxifloxacin is the recommended and most commonly used antibiotic (12,47), but reports of resistance are emerging (50).…”
Section: Discussionmentioning
confidence: 99%
“…Most early studies have shown insufficient microbiological and clinical cure rates with tetracyclines, whereas azithromycin (1-g single dose) appeared to be superior but far from perfect, with cure rates rarely exceeding 85% (16)(17)(18). However, more recent randomized clinical trials from the United States have shown a decreasing cure rate after azithromycin 1-g single-dose therapy, with a microbiological cure rate of 67% among patients included between 2006 and 2009 (19) reduced to 40% among patients included between 2007 and 2011 (20). Moxifloxacin is currently the most commonly used second-line antibiotic in patients failing azithromycin treatment (11,21).…”
mentioning
confidence: 99%